Blastic plasmacytoid dendritic cell neoplasm is dependent on BCL-2 and sensitive to venetoclax - Montero, Joan (Cancer Discov, 2016)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an aggressive hematologic malignancy with dismal outcomes for which no standard therapy exists. We found that primary BPDCN cells were dependent on the anti-apoptotic protein BCL-2 and were uniformly sensitive to the BCL-2 inhibitor venetoclax, as measured by direct cytotoxicity, apoptosis assays, and dynamic BH3 profiling. Animals bearing BPDCN patient-derived xenografts had disease responses and improved survival after venetoclax treatment in vivo. Finally, we report on two patients with relapsed/refractory BPDCN who received venetoclax off-label and experienced significant disease responses. We propose that venetoclax or other BCL-2 inhibitors undergo expedited clinical evaluation in BPDCN, alone or in combination with other therapies. In addition, these data illustrate an example of precision medicine to predict treatment response using ex vivo functional assessment of primary tumor tissue, without requiring a genetic biomarker.